Plant Pathogenic Microorganisms: State-of-the-Art Research in Spain - Elvira Fiallo-Olivé; Ana Palacio-Bielsa; Soledad Sacristán (Microorganisms, 2023)
Pathogenic microorganisms, including fungi, oomycetes, bacteria, viruses, and viroids, constitute a serious threat to agriculture worldwide [...]